Inclusion of persons with disabilities in higher education: a study on Argentina, Brazil and Paraguay - Gomes da Silva, Ivanir; Pasini, Juliana de Fatima Serraglio; Soligo, Valdecir (Debates em Educação, 2023)
This research refers to the comparative study of educational policies for the inclusion of people with disabilities in higher education, focusing on the policies developed by the federal education systems of the following countries: Argentina, Brazil and Paraguay.